(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
In the fauna of animals living in nature, vertebrates, although systematically classified as chordates, are much less numerous than invertebrates, and differ sharply from them in their large body size, complex and diverse structure of individuals, and the diversity of physiological and ecological characteristics. Therefore, chordates are of incomparably great importance in human life and livelihoods, and are hunted for their meat, skin, fur, eggs and oil. Therefore, the preservation of rare and endangered vertebrate fish species through ecology, developmental characteristics, reproduction, migration, protection and breeding technologies is one of the most urgent issues, and fish are not only a reliable source of food for humans, but also a valuable raw material.